Strategi Transformasi Digital dalam Meningkatkan Daya Saing UMKM: Sebuah Kajian Konseptual - Yeni Sulastri (Jurnal Ilmu Sosial, Ekonomi dan Pendidikan, 2026)
Digital transformation has become a crucial factor in strengthening the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) amid rapid technological advancements and changing consumer behavior. This study aims to analyze digital transformation strategies that can enhance the competitiveness of MSMEs in a sustainable manner. The research employs a qualitative approach using a literature review method by examining scientific articles, international reports, and policy documents published between 2021 and 2026. Data were analyzed descriptively to identify internal and external factors influencing successful digital transformation. The findings indicate that successful digital transformation depends on five strategic dimensions: improving digital literacy, utilizing digital platforms for marketing and transactions, adopting digital technologies in business operations, fostering product innovation based on market demand, and strengthening collaboration among government, academia, the private sector, and business communities. Digital transformation improves operational efficiency, expands market access, enhances service quality, strengthens customer relationships, and creates sustainable competitive advantages. This study proposes a conceptual framework integrating human resources, technology adoption, innovation capability, collaborative networks, and policy support as key pillars for enhancing MSME competitiveness. The findings provide valuable insights for policymakers and business practitioners in designing sustainable digital transformation programs for MSMEs.